Holocene history of a raised bog, northern New Zealand, based on plant cuticles. (February 2017) - Haenfling, Carolin; Newnham, Rewi; Rees, Andrew; Jara, Ignacio; Homes, Aline; Clarkson, Beverley
We present a method for analysing subfossil plant cuticles preserved in peat and apply the method to provide a preliminary, coarse resolution reconstruction of Holocene vegetation history at Moanatuatua Bog, northern North Island, New Zealand. The plant cuticle record reveals the early-Holocene development of a swamp and its transition to a raised bog, which is not apparent from other proxies. Comparison with a pollen record from the same sequence highlights the advantages of plant cuticle analysis in cases where pollen is hard to identify or poorly preserved. In particular, distinguishing between the pollen grains of the two main bog species, the restiads Empodisma robustum and Sporadanthus ferrugineus, relies on subtle gradational characteristics, whereas their cuticular patterns are very distinct. Furthermore, Cyperaceae pollen is poorly preserved at Moanatuatua Bog, being almost completely absent, whereas the Cyperaceae cuticles are present throughout the sequence. Therefore, we suggest that Cyperaceae pollen at this site is a less reliable indicator of local sedge communities than the cuticle record. The wide dispersal capabilities of these wind-dispersed pollen types also make them less suitable for determining local site vegetation and environmental change in comparison with cuticle remains. These results suggest that plant cuticle analysis may be a useful tool for the reconstruction of long-term vegetation changes from peat sequences, especially when used in concert with palynology. Sample preparation also proved to be fast with little equipment or chemicals needed.